Stakeholders Behaviour towards Clean India Mission’s New Municipal Solid Waste Collection System in Chandrapur City, Central India - Kamble, R. K.; Nimgade, Namrata R.; Patil, Priyanka V. (International Journal of Environment, 2017)
The study was carried out to analyze behavioural pattern of stakeholders–inhabitants of Chandrapur city as well as employees of Chandrapur Municipal Corporation (CMC)–towards the "Clean India Mission" scheme as compared with previous scheme of women’s self help group. For behavioural change analysis field survey was carried out in October 2015 in Chandrapur city. Total 41 respondent including inhabitants and employees of CMC were interviewed. The results of the study shows that, previously municipal solid waste (MSW) collection was irregular (41.66%) however, since the implementation of this new scheme it has become regular (100%). Enhanced MSW collection frequency was observed (once a day, 83.33%) with alternative staff arrangement in case of staff is absent. The work was monitored by officials (79%) which were previously not existing. In previous scheme, extra money was charged for collection of MSW, however no such charges are levied in this new scheme. Satisfaction rate of this new scheme was 95.83% among inhabitants. As reported by MSW collection employees, there was awareness among inhabitants about dry and wet waste (41.17%). The employees were satisfied with the scheme (94.11%) as there is improved and timely salary with a job guaranty. INTERNATIONAL JOURNAL OF ENVIRONMENT Volume-5, Issue-4, Sep-Nov 2016, page: 32-43